Strategi Memanfaatkan Rasa Senang Anak Bersekolah (Studi Berdasarkan Tingkat Pendidikan Orang Tua DI Pangkalan Bun Kalimantan Tengah) - Muslimah Muslimah (Jurusan Tarbiyah,IAIN PALANGKARAYA, 2020)
This study aims to analyze how children's acceptance begins school; and how parents' strategies to maintain the fun of children early in school. This qualitative research was explored through observation techniques to parents in utilizing children's sense of schooling; and interviews with parents as research subjects, and also to children as informants and subanalysis of research on the acceptance of children attending school and parents' tips in utilizing the joys of children attending school; and family documentation to see the child's age of birth. This research is analyzed systematically through theories relating to pedagogy and psychology. The research findings show: all children have the same acceptance, that is; feeling happy when starting formal schooling in the elementary school; the strategy of parents with high school education and scholars who is using and conditioning consciously the joys of children in school; and parents who have junior high school education submit to children through teacher guidance; and parents who have an elementary school education fully surrender to children without guidance.